Derivational Versus Phrasal Adverbials of Manner - Protopopescu Daria (Romanian Journal of English Studies, 2014)
This paper compares the usage of derivational and phrasal adverbial expressions of manner in English and Romanian. It also points to possible translational and learning problems due to selection peculiarities in the two languages. Both English as well as some of the Romance languages (among others French, Italian, Spanish), use both simple adverbs of manner (e.g. well) and derivational adverbs formed by adding a suffix to an adjective (e.g. poorly vs -mente adverbs in Romance).